UPAYA MENINGKATKAN HASIL BELAJAR BIOLOGI MELALUI PENERAPAN PEMBELAJARAN KOOPERATIF TIPE JIGSAW PADA SISWA KELAS X1 MAN LUWU KAB. LUWU - Erniati m (STKIP Pembangunan Indonesia Makassar, 2023)
This research is a classroom action research aimed at improving student biology learning outcomes through the application of Jigsaw cooperative learning. The study was conducted at MAN Luwu Kab. Luwu in the Odd semester of the academic year 2022/2023 in November 2022 with the Research Subject is a class X1 student consisting of 25 students. The study consists of 2 cycles and the collected data is analyzed using quantitative analysis. The results of the research show that the application of cooperative learning Jigsaw is an effective learning model for improving the biological learning outcomes of students of class X1 MAN Luwu Kab. Luwu. The increase was demonstrated by the results of the study from Cycle I to Cycle II, i.e. the average student learning outcome score increased from 71.00 from the ideal score of 100 with a standard deviation of 2.79 to 79.40 from the optimal score of 100, with a deviation standard of 1.69 as well as the increase in the percentage of strict students from 56% to 84%. From the results of this study can be concluded that there was an increase in the learning outcome of students of class X1 MAN Luwu kab. Luwu through the application of cooperative learning type Jigsaw. Keywords: Biology learning results, Jigsaw cooperative learning